CSR DAN PROFITABILITAS: STUDI EMPIRIS PADA SEKTOR INDUSTRI DASAR DAN KIMIA TAHUN 2015–2019 - Chandra, Agetha (Media Akuntansi dan Perpajakan Indonesia, 2022)
This study was conducted to determine the effect of corporate social responsibility on company profitability, especially return on assets (ROA). This study uses 3 independent variables, namely CSR-economy (X1), CSR-environment (X2), and CSR-social (X3). The dependent variable in this study is only 1 which is return on assets (Y). The type of data in this study is secondary quantitative with a sampling technique using purposive sampling with criteria for basic and chemical industrial companies that have sustainability reports and annual reports for 2015–2019. The data analysis technique uses multiple linear regression using SPSS 25. In this study, the following results were obtained: CSR-economic has no effect on ROA, CSRenvironment has no effect on ROA, and CSR-social has a negative effect on ROA.